Program to Eradicate Malaria in Sardinia, 1946–1950 - Eugenia Tognotti (Emerging Infectious Diseases, 2009)
During 1946–1950, the Rockefeller Foundation conducted a large-scale experiment in Sardinia to test the feasibility of indigenous vector species eradication. The interruption of malaria transmission did not require vector eradication, but with a goal of developing a new strategy to fight malaria, the choice was made to wage a rapid attack with a powerful new chemical. Costing millions of dollars, 267 metric tons of DDT were spread over the island. Although malaria was eliminated, the main objective, complete eradication of the vector, was not achieved. Despite its being considered almost eradicated in the mid-1940s, malaria 60 years later is still a major public health problem throughout the world, and its eradication is back on the global health agenda.